2002
DOI: 10.1080/14634980290032018
|View full text |Cite
|
Sign up to set email alerts
|

Soft sediment as a constraint on the spread of the zebra mussel in western Lake Erie: Processes and impacts

Abstract: The zebra mussel (Dreissena), inadvertently introduced to the Great Lakes in 1986, has since expanded to cover most of the shallow-water, hard substrates in Lakes Erie and Ontario. Colony densities exceed 300,000 per m2 in some bedrock areas of western Lake Erie. The objective of this study was to investigate the spread of zebra mussel onto soft sediment areas of the western basin of Lake Erie and to identify natural controls on the large-scale colonization of such sediments. Combined side scan sonar, underwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Mussel densities at this site in 1998 and 2003 were near 20 000 m −2 (22 239 and 20 847 m −2 , respectively; Pontius, 2000; Fig. 3a), whereas other studies have found much lower mussel densities (<500 m −2 on mud; Coakley et al. , 2002) or much higher (270 000 m −2 on rocks, MacIsaac et al.…”
Section: Resultsmentioning
confidence: 61%
“…Mussel densities at this site in 1998 and 2003 were near 20 000 m −2 (22 239 and 20 847 m −2 , respectively; Pontius, 2000; Fig. 3a), whereas other studies have found much lower mussel densities (<500 m −2 on mud; Coakley et al. , 2002) or much higher (270 000 m −2 on rocks, MacIsaac et al.…”
Section: Resultsmentioning
confidence: 61%
“…Between 1999 and 2004, lakewide biomass of zebra and quagga mussels ranged from 14 kt (1,000s of metric tones) in 1999 to a peak of 43 kt in 2001 and returned to 14 kt in 2003 (Madenjian et al 2005a). These lakewide estimates are likely conservative because trawls are not fished over the hard substrate on which zebra mussels prefer to attach Coakley et al 2002). Zebra mussel biomass was not separated from quagga mussel biomass in these trawl surveys, but observations suggest that the proportion of quagga mussels has been increasing in recent years.…”
Section: Zebra and Quagga Musselsmentioning
confidence: 96%
“…Unfiltered lake water with naturally occurring plankton was refreshed about twice a week in the stock tubs of Dreissena to provide food and other resources. The quantity of undamaged Dreissena added to the experimental tanks represented the density of Dreissena on soft sediments in Lake Erie (i.e., 3,400 individuals m -2 (Coakley et al, 2002) or 116 individuals/tank). Empty Dreissena clusters were made by attaching dead Dreissena shells together using small beads of non-toxic glue to provide the same physical structure as live Dreissena, without any contribution of resources from active metabolism.…”
Section: Experimental Set-up and Designmentioning
confidence: 99%
“…Shallow freshwater environments and areas of dense algal mats can become depleted in CO 2 (Stevenson, 1988;Stevenson et al, 2004), which can restrict photosynthesis if the alga cannot utilize HCO 3 -as well as CO 2 (Cheney & Hough, 1983). Dreissena aggregations can have a very high density (Coakley et al, 2002); consequently, CO 2 produced by their respiration and the decomposition of their waste may potentially increase CO 2 and soluble organic carbon within the benthos. Although studies have shown that Dreissena can promote benthic algal blooms through increased light, P, and N, the relative importance of potential flows of macronutrients and carbon (C) from Dreissena to algae on controlling benthic primary production has not been shown.…”
Section: Introductionmentioning
confidence: 97%